Success rate of fractured teeth receiving modified crown lengthening surgery and restorations - Cui Wang; Xue-ting Jia; Min Zhen; Wen-Jie Hu; Hao Zhang; Kwok-Hung Chung (BMC, 2022)
Abstract Background Whether to preserve a structurally compromised tooth or remove it is a dilemma often encountered by clinicians. The aim of this study was to assess the long-term success rate of fractured teeth preserved by modified crown lengthening surgery and restorations. Methods Thirty-nine patients with a total of 45 fractured teeth who had received modified crown lengthening surgery were recruited and examined. Numbers of teeth lost were recorded, and the criteria for successful teeth were defined. Kaplan-Meier estimator was used to determine the success rate. Possible risk factors were compared between successful and unsuccessful groups by a Cox regression analysis to explore the potential predictors of failure with a significant level at α = 0.05. Results The mean ± SD of success time without considering variants was 6.2 ± 0.6 years (95% CI 5.1-7.7). The mean survival rates ± SD at 1.0-, 2.0-, 3.0-, 5.0-, 7.0-, and 9.0-year intervals was 97.8 ± 2.2%, 92.2 ± 4.4%, 72.8 ± 7.9%, 68.2 ± 8.6%, 60.7 ± 10.5%, and 40.4 ± 13.6%, respectively. Failure cases in teeth with poor plaque control and step-shaped fracture margin were significantly more than those with good plaque control and knife-shaped fracture margin (HR = 7.237, p = 0.011; HR = 15.399, p = 0.006; respectively). Conclusions Fractured teeth treated with modified crown lengthening surgery are anticipated to have a high clinical success rate for 6.2 ± 0.6 years. Plaque control and fracture morphology appeared to be significantly associated with the success of the multidisciplinary treatment approach.